A Laporan Kasus: Wanita 58 Tahun dengan Ptosis Oculi Sinistra et causa Paresis Nervus Oculomotor (CN III) Incomplete-Without Pupillary Involvement - Alfia Nikmah; Sisca Mayasari (Medula, 2021)
Ptosis is a condition when the palpebrae drop from their normal position. Ptosis describes the dropping of the upper eyelid  so that it covers half or all of the pupils which can disturb the vision. This condition got worse in downgaze position. Based on its onset, ptosis is divided into congenital and acquired. Neurogenic ptosis is the most common aquired ptosis, mainly due to paresis oculomotor nerve (CN III). In the elderly, it is necessary to suspect the paresis due to ischemia, especially in patients with underlying systemic disease. This case report describes a 48 year old woman with the chief complaint of painless upper eyelids ptosis since 4 months ago. Initially it was only partially closed, and the last 2 months it became completely closed. Visual acquity of the left eye  6/60, eye movements were full, pupil were equal and reactive, Relative Afferent Pupillary Defect (RAPD) were not found, and normal Bell’s phenomenon. Margin Reflex Distance (MRD)-1 score-5 mm, Interpalpebral Fissure (IPF) score 0 mm, and  poor levator function 0 mm. The anterior segment is within normal limits. Laboratory tests, head CT scan, and MRI were within normal limits. Based on the results of the history, ophthalmological examination, and investigations, the patient was diagnosed with ptosis ocular sinistra et causa nerve oculomotor (CN III) paresis incomplete-without pupillary involvement. The patient get non-steroidal anti-inflammatory drugs, observation, and planned for frontalis sling surgery.